Virus Infection, Genetic Mutations, and Prion Infection in Prion Protein Conversion - Hideyuki Hara (MDPI AG, 2021)
Conformational conversion of the cellular isoform of prion protein, PrPC, into the abnormally folded, amyloidogenic isoform, PrPSc, is an underlying pathogenic mechanism in prion diseases. The diseases manifest as sporadic, hereditary, and acquired disorders. Etiological mechanisms driving the conversion of PrPC into PrPSc are unknown in sporadic prion diseases, while prion infection and specific mutations in the PrP gene are known to cause the conversion of PrPC into PrPSc in acquired and hereditary prion diseases, respectively. We recently reported that a neurotropic strain of influenza A virus (IAV) induced the conversion of PrPC into PrPSc as well as formation of infectious prions in mouse neuroblastoma cells after infection, suggesting the causative role of the neuronal infection of IAV in sporadic prion diseases. Here, we discuss the conversion mechanism of PrPC into PrPSc in different types of prion diseases, by presenting our findings of the IAV infection-induced conversion of PrPC into PrPSc and by reviewing the so far reported transgenic animal models of hereditary prion diseases and the reverse genetic studies, which have revealed the structure-function relationship for PrPC to convert into PrPSc after prion infection.